Maternal COVID-19 vaccine acceptance among Malaysian pregnant women: A multicenter cross-sectional study - Kalok, Aida; Razak Dali, Wira; Sharip, Shalisah; Abdullah, Bahiyah; Kamarudin, Maherah; Dasrilsyah, Rima Anggrena; Abdul Rahman, Rahana; Kamisan Atan, Ixora (Frontiers Media, 2023)
Introduction: The coronavirus disease 2019 (COVID-19) caused a global pandemic that resulted in devastating health, economic and social disruption. Pregnant mothers are susceptible to COVID-19 complications due to physiological and immunity changes in pregnancy. We aimed to assess the maternal vaccine acceptance of the COVID-19 vaccine. Methods: A multi-center study across four teaching hospitals in the Klang Valley, Malaysia was conducted between September 2021 and May 2022. A survey was conducted using a self-administered electronic questionnaire. The survey instruments included; (1) maternal perception and attitude toward COVID-19 vaccination, (2) COVID-19 pregnancy-related anxiety, and 3) generalized anxiety disorder. Results: The response rate was 96.6%, with a final number for analysis of 1,272. The majority of our women were Malays (89.5%), with a mean age (standard deviation, SD) of 32.2 (4.6). The maternal vaccine acceptance in our study was 77.1%. Household income (p < 0.001), employment status (p = 0.011), and health sector worker (p = 0.001) were independent predictors of maternal willingness to be vaccinated. COVID-19 infection to self or among social contact and greater COVID-19 pregnancy-related anxiety were associated with increased odds of accepting the SARS-CoV-2 vaccine. Women who rely on the internet and social media as a source of vaccine information were more likely to be receptive to vaccination (adjusted odd ratio, AOR 1.63; 95% CI 1.14–2.33). Strong correlations were observed between maternal vaccine acceptance and the positive perception of (1) vaccine information (p < 0.001), (2) protective effects of vaccine (p < 0.001), and (3) getting vaccinated as a societal responsibility (p < 0.001). Discussion: The high maternal vaccine acceptance rate among urban pregnant women in Malaysia is most likely related to their high socio-economic status. Responsible use of the internet and social media, alongside appropriate counseling by health professionals, is essential in reducing vaccine hesitancy among pregnant women.